2018
DOI: 10.1038/s41598-018-23611-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome-wide analysis of extracellular small RNAs from the mucormycosis pathogen Rhizopus delemar

Abstract: Rhizopus delemar is an emerging fungal pathogen causing devastating mucormycosis in immunocompromised individuals. The organism remains understudied and there are urgent needs for new methods of rapid disease diagnosis for timely therapy. Extracellular vesicles with encapsulated RNAs have recently been discovered to have great potential applications for disease diagnoses and treatments. To explore the utilization of ex-RNA in studies of mucormycosis, we have performed RNA-Seq of ex-sRNAs from two clinical stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…These molecules can contain a variety of molecules, including small RNAs (Peres da Silva et al, 2015). Transcriptomic analysis on EVs from two clinical strains of R. delemar showed an abundance of extracellular small RNAs (exRNAs) that varied in types and length (Liu et al, 2018). Prediction programs for miRNA suggested that the majority of secreted miRNA targeted host genes, specifically those related to carbohydrate metabolism, secondary metabolite biosynthesis, and the two-component system.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…These molecules can contain a variety of molecules, including small RNAs (Peres da Silva et al, 2015). Transcriptomic analysis on EVs from two clinical strains of R. delemar showed an abundance of extracellular small RNAs (exRNAs) that varied in types and length (Liu et al, 2018). Prediction programs for miRNA suggested that the majority of secreted miRNA targeted host genes, specifically those related to carbohydrate metabolism, secondary metabolite biosynthesis, and the two-component system.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…While disease can be caused by several species in the Mucorales order, Rhizopus delemar and Rhizopus microsporus are responsible for the majority of infections (Liu et al 2018). Risk factors for developing the disease include, but are not limited to: innate immune cell deficiencies, uncontrolled diabetes, immune suppression, skin barrier breaches and iron overload (Baldin & Ibrahim 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Current antifungal treatments are ineffective, resulting in the reliance upon surgical debridement of infected tissues ( 30 ), often leading to long-term disability. Disease can be caused by several species of the Mucorales order; however, Rhizopus delemar , previously known as Rhizopus oryzae , accounts for 70% of cases ( 31 ). Spores are the infectious agents of mucormycosis.…”
Section: Introductionmentioning
confidence: 99%